Evaluation of empirical titration equivalents of certain types of industrial surfactants determinable by potentiometric titration with sodium tetraphenylborate - Kormali Ertürün, H. Elif; Mikysek, Tomáš; Vytřas, Karel (Univerzita Pardubice, 2018)
In this study, it has been shown that potenciometric titration using sodium tetraphenylborate as the titrant can be used as a simple and inexpensive method for the determination of some industrial surfactants commonly used in detergents. Examples of determination of some cationic and non-ionic surfactants and related calculations are given.
Vyhodnocení empirických titračních ekvivalentů určitých typů průmyslových povrchově aktivních látek stanovitelných potenciometrickou titrací tetrapenylboritanem sodným
Keywords: Surfactants; potentiometric titration; sodium tetraphenylborate; Povrchově aktivní látky; potenciometrická titrace; tetrafenylboritan sodný